The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1200/jco.2010.33.3179
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Prescription Co-Payment Amount and Compliance With Adjuvant Hormonal Therapy in Women With Early-Stage Breast Cancer

Abstract: A B S T R A C T PurposeNoncompliance with adjuvant hormonal therapy among women with breast cancer is common. Little is known about the impact of financial factors, such as co-payments, on noncompliance. Patients and MethodsWe conducted a retrospective cohort study by using the pharmacy and medical claims database at Medco Health Solutions. Women older than age 50 years who were taking aromatase inhibitors (AIs) for resected breast cancer with two or more mail-order prescriptions, from January 1, 2007, to Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
250
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(261 citation statements)
references
References 52 publications
(34 reference statements)
9
250
2
Order By: Relevance
“…Among the variety of methods to estimate the A & P, those based on retrospective data are still more used due to their easiness of calculation and low cost, besides presenting closer rates to the real ones, when compared with studies that use direct methods to determine such behaviors 14,28,29 . Regarding persistence estimates, we need to relativize the results, given the adopted concept considers the interruption of treatment for more than or 60 days.…”
Section: Discussionmentioning
confidence: 99%
“…Among the variety of methods to estimate the A & P, those based on retrospective data are still more used due to their easiness of calculation and low cost, besides presenting closer rates to the real ones, when compared with studies that use direct methods to determine such behaviors 14,28,29 . Regarding persistence estimates, we need to relativize the results, given the adopted concept considers the interruption of treatment for more than or 60 days.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with cancer experience greater financial burden, higher out-ofpocket expenses, and are at increased risk for bankruptcy compared with patients without cancer [17,21]. Additionally, studies have demonstrated that patients experiencing financial burden may jeopardize their medical care by forgoing recommended treatments [22][23][24]. Thus, the financial burden experienced by patients with cancer has been called a toxic side effect of their care [19].…”
Section: Introductionmentioning
confidence: 99%
“…High out-of-pocket costs have been cited as one possible reason for inadequate use of oral cancer therapies [19,20]. For example, chronic myeloid leukemia is a condition for which even small lapses in adherence are associated with poor outcomes.…”
Section: Making Treatments More Affordable To Patientsmentioning
confidence: 99%